Investigate the Academic Challenges Encountered By Learners with Visual Impairment (Contemporary Journal of Social Science Review, 2024)
The study was carried out to evaluate the academic challenges encountered by learner with vision impairment. The explored the challenges faced by visual impairment student in community, in classroom setting, and the financial challenges. The study was descriptive in nature. All the learners with visual impairment presently studying in the govt. special education schools of district Faisalabad were the population of the study. A sample of 50 learners with visual impairment was selected for the study who was currently studying in the govt. special education schools in district Faisalabad. The questionnaire for the learner with vision impairment contained 22 questions. The research tool was designed with the help of supervisor and other faculty members for having reliable and valid results. The entire questionnaires were collected back at the spots. The collected data was analyzed using frequency and percentage. It was inferred that learners with visual impairment had community challenges such as poor orientation and mobility training, non-provision of assistance by the people in their routine workings. Academic challenge of the learners with visual impairment incorporated the poor provision of educational materials (charts, graphs or diagrams etc.), lack of effective availability of Braille books and Braille reading material, lack of Braille embosser, and lack library resources. The financial resources were required to be provided for the provision of computer and internet for the learners with visual impairment. Future research may be carried out to investigate the challenges encountered by the learners with visual impairment at higher education level.